Destructive Leadership in Sports: Developing the Sports Coaching Destructive Leadership Scale (Sc-Dls) - uymaz, ali; Karagözoğlu, Cengiz; Türegün, Emre; Baba, Adem (Advances in Social Sciences Research Journal, 2016)
This study investigates the validity and reliability of the Destructive Coaching Leadership Scale according to athletes. All athlete participants were asked to fill a personal information form and the Destructive Coaching Leadership Scale developmental version, which consists of 72 items. 360 athletes from several disciplines who have competed for one or more years with their team coaches asked to join to the study, 338 of participants answered the scale and personal information form, 18 of the filled forms were excluded by researchers. The Final research sample consisted of 320 active athletes (214 male and 106 female). According to the principal components factor analysis of five factors, which are I-Planning and Change Management, II-Fear of Failure-Pressure, III- Emotional Ambivalence, IV-Distrust and V-Democratic Behavior were extracted.